2011
DOI: 10.1007/s10096-011-1407-7
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial infections in adult patients with hematological malignancy

Abstract: We retrospectively analyzed the clinical and microbiological characteristics of adult patients with hematological malignancy and nontuberculous mycobacteria (NTM) infections from 2001 to 2010. During the study period, 50 patients with hematological malignancy and tuberculosis (TB) were also evaluated. Among 2,846 patients with hematological malignancy, 34 (1.2%) patients had NTM infections. Mycobacterium avium-intracellulare complex (13 patients, 38%) was the most commonly isolated species, followed by M. absc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…20 Table 1 (Table S1 for full table) shows the study and patient characteristics of studies on pulmonary NTM disease (n = 13) and studies on both pulmonary and extra-pulmonary NTM diseases combined (n = 4). Studies examined the following outcomes: HRQOL alone (n = 2), 21,22 comorbidities alone (n = 1), 23 mortality alone (n = 11), 20,[24][25][26][27][28][29][30][31][32][33] and both comorbidities and mortality (n = 3). 9,34,35 The earliest study date was 1990 while the remaining spanned from 2003 to 2014.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Table 1 (Table S1 for full table) shows the study and patient characteristics of studies on pulmonary NTM disease (n = 13) and studies on both pulmonary and extra-pulmonary NTM diseases combined (n = 4). Studies examined the following outcomes: HRQOL alone (n = 2), 21,22 comorbidities alone (n = 1), 23 mortality alone (n = 11), 20,[24][25][26][27][28][29][30][31][32][33] and both comorbidities and mortality (n = 3). 9,34,35 The earliest study date was 1990 while the remaining spanned from 2003 to 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies examined populations with other underlying conditions. In haematological malignancy (n = 84), 26 30-day survival was worse in those with pulmonary and extra-pulmonary NTM than TB (log-rank test: P = 0.03). In rheumatoid arthritis (n = 124 019), 25 the odds of dying by the end of followup were 81% greater (HR (95% CI): 1.81 (1.5-2.1)) in pulmonary and extra-pulmonary NTM disease.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the clarithromycin MIC values of 33 of 36 M. massiliense isolates were Յ2 g/ml when the broth susceptibility test results were read on day 5; however, 11 (33.3%) of the 33 isolates exhibited clarithromycin MICs of Ͼ16 (Ն32) g/ml during the 14-day observation. Previous studies have shown that rapidly growing mycobacteria, especially those of the M. abscessus complex, are the most common clinical isolates of mycobacteria and are a major cause of pulmonary disease due to nontuberculous mycobacteria (NTM) in Asia (2,3,(18)(19)(20). Saleeb et al reported that MALDI-TOF MS can be incorporated into the work flow of the microbiology laboratory for rapid and accurate identification of most species of mycobacteria (16).…”
mentioning
confidence: 99%